Human Cytomegalovirus US7 Is Regulated Synergistically by Two Virally Encoded MicroRNAs and by Two Distinct Mechanisms - Tirabassi, Rebecca (American Society for Microbiology, 2011)
Human cytomegalovirus (HCMV) encodes at least 14 microRNAs (miRNAs) that act posttranscriptionally to repress gene expression. Although several HCMV miRNA targets of both cellular and viral origin have been identified, our knowledge of their function remains limited. HCMV miRNA targets, as well as phenotypes associated with HCMV miRNA mutants, have been difficult to identify since the downregulation of targets by a single miRNA is often less than 2-fold. Several factors can contribute to the strength of repression, including the mechanism of translational inhibition, the degree of complementarity between the miRNA and target mRNA, the number of binding sites for one miRNA, and cooperativity or antagonism between miRNAs. To determine the effect of multiple miRNAs on one gene, we examined the repression of a viral gene, US7. Here we demonstrate that the HCMV-encoded miRNAs miR-US5-1 and miR-US5-2 function in a highly synergistic manner to regulate US7, even at very low miRNA concentrations. Regulation of US7 involves three functional miRNA binding sites: two that are completely complementary to the 3′ untranslated region (3′UTR) and one that is imperfectly matched. Surprisingly, we observed equal contributions to inhibition from both complete and partially complementary sites, and repression was not completely abrogated until all three sites were mutated simultaneously. We also observed that the miRNA binding sites did not follow the spacing constraints for corepressive miRNAs observed in earlier reports. These results underscore the importance of evaluating the contribution of multiple miRNAs on gene regulation and shed new insight into miRNA:mRNA interactions.